Directions for the recovery of agricultural production on radioactively contaminated lands - Kustovska О.; Lebedeva, E. (Land Management, Cadastre and Land Monitoring, 2017)
. Effective management of agricultural production in the Polesie Ukraine traditionally was complicated through the low natural land fertility, their high acidity, perevolotsky valley. During the centrally planned economic system that the natural contrast of the Polesie land had been somewhat neglected by the state through differentiation of purchase prices for agricultural products, which gave the possibility of redistribution of the rent in favor of the farms with poorer land. With transition to market relations the role of the state, and hence the possibility of its influence on this situation has changed dramatically. Economic conditions have become more profitable for the farmers that are occupying the best lands. However, the situation in the regions has not yet been investigated systematically taking into account the modern complex socio-economic processes and phenomena caused by increased environmental stress on land resources. One of the most pernicious environmental effects of the Chernobyl accident was radioactive contamination of agricultural land, defined in the final stage of transfer of radionuclides in the human body and further irradiation. The main danger of the accumulation by plants of radionuclides lies in the fact that they are a major link in the migratory chain of transmission of radionuclides to the more radiosensitive species and, above all, human. Economic feature of agricultural production in the study area is insufficient pricesambien, transformation of land use, violations of industrial-economic relations, the structure of agricultural production, changes in the natural-cost structure commodity products, the reform of the organizational structure of agricultural production. In the farms located in contaminated areas, the necessary conversion of dairy cattle for meat. In conditions of high pollution, the production of milk requires a serious sanitary objections in that time, as meat production is more environmentally friendly. The suspension of activities and the provision of radioactively clean food products led to the growth of volumes of consumption of contaminated food of local production, the increase in the number of people exceeding the doses of internal irradiation and the deterioration of the health status of the people of radioactively contaminated territories. The main component of the mechanism by contaminated land is agricultural activities (placement of crops, depending on the ability to accumulate radionuclides, soil treatment), agrochemical activities (liming of acidic soils, application of mineral and organic fertilizers and the use of sorbents, change of mode of feeding of animals and processing of animal products to reduce the content of radionuclides. Of course, the above list of events is far from complete, this is only the basic that require mandatory implementation in agricultural production. Among the measures of rehabilitation of polluted areas leading place belongs to the radical improvement of meadows and pastures, which in turn requires a considerable amount of seeds of cereals and legumes. The analysis of economic efficiency of growing of the testes, including radioactively contaminated region shows that even in marginal soils of Polesye in low yield of the seed farms have substantial profits. On soils with acidity the most common and affordable event reduce radionuclide accumulation in products is liming, which not only reduces the accumulation of radionuclides in agricultural crops but also improves soil fertility, increases yield and contributes to the dilution of radionuclides per unit mass of crop production. Only a comprehensive use of differentiated areas of contaminated land will allow some measure to improve the ecological situation on the territory of the object. Key words: restoration of radioactively contaminated land, soil, agricultural products, ecological state.